An Integrated Model of Shared Leadership on Entrepreneurial Team Performance : Evidence From Indonesia - Andika; Radityo Putro Handrito; Ana Sofia Aryati (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
Building an entrepreneurial enterprise with a team is a dynamic process and requires effective teamwork. Thus, The idea of shared leadership as a team leadership approach is crucial. Based on social exchange theory, Through knowledge sharing as a moderator and team trust and creativity as a mediator, we examine how shared leadership might enhance team performance. To test our hypotheses, data were collected from 71 entrepreneurial teams (306 members and 73 supervisors) through combined online and offline surveys. Aggregated at the team level, Smart PLS 3.0 was used to analyze the data and evaluate the suggested model. Findings reveal that team performance is greatly improved by shared leadership, with trust and creativity partially mediating this effect. Contrary to expectations, knowledge sharing did not moderate the relationship This study advances the literature by introducing team creativity as a previously underexplored mediating mechanism in the link between team performance and shared leadership. Moreover, the use of dyadic data from both leaders and team members strengthens the methodological rigor by mitigating common method bias and enhancing the robustness of the findings. The findings highlight the critical role of building trust and encouraging creativity in boosting team effectiveness, providing meaningful insights for improving entrepreneurship programs in Indonesia and promoting long-term success.